Films for Use in Canadian Industry - Hill, Rowland (Relations industrielles / Industrial Relations, 1952)
In this article, the author emphasizes that moving-pictures, formerly identified with entertainment and more recently as an aid to education, have been used by industry, but that there still remains much to do to cover the field of usefulness of the film itself. Movies had an active part during the war and should continue this function during peace. The Federal Department of Labour is attempting to promote a wider use of movies concerned with the field of labour and is doing this by means of a catalogue and films supplement, of filmstrips and of library. The author, moreover, suggests the different possible sources for obtaining available films.